Implementasi Program Pendampingan Desa dalam Bidang Pertanian - Esi Sumarni; Rosidin Rosidin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study reviews the implementation of the Village Assistance Program in Agriculture in Rimba Besar Village, Semidang Alas Maras District, Seluma Regency. This research uses descriptive qualitative method. Research conducted by describing a situation or event in the field based on events that have occurred. This study aims to find out what are the village assistance programs in agriculture in Rimba Besar Village, Semidang Alas Maras District, Seluma Regency. This problem can be seen from the general picture that the implementation is still not optimal, in terms of the distribution of rice seeds for food crops, usually the distribution of seeds is carried out every 1 year 2 times in 2020 the distribution of rice seeds but what happens in 2021 the distribution of rice seeds is no longer running, and also using rice milling facilities, which are free of charge for rice milling, only for machine maintenance, but the reality is that the community is still charged for the rice milling. The data in this study were obtained through observation, interviews, and documentation. The results of this study indicate that the implementation of the village mentoring program has been going well, based on the indicators of the implementation of the village assistance program according to M.S Grindlel 1) the resources involved, 2) the benefits obtained 3) the changes achieved. Keywords: Program Implemation, Village Assistance, In Agriculture